A new species of Notomulciber (Micromulciber) Aurivillius, 1913, from the southern Western Ghats of India (Coleoptera: Cerambycidae: Lamiinae: Homonoeini) - Hiremath, S. R. (Zootaxa, 2018)
Notomulciber (Micromulciber) viraktamathi sp. nov. is described and illustrated from the southern Western Ghats, a hotspot of biodiversity in India. Ecological notes, differential diagnosis of the new species from its close relatives and a key to the species of Notomulciber from India are provided.